(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the lyrical heritage of Shermuhammad Munis, one of the artists who left an indelible mark in the history of the Khanate of Khiva at the beginning of the 19th century. The world of themes of the poet’s ghazals, issues of artistic skill are analyzed.